Precautions in postmortem examinations in Covid-19 - Related deaths: Recommendations from Germany. (July 2020) - Keten, Derya; Okdemir, Erdem; Keten, Alper
Abstract: The Covid-19 pandemic is also a considerable risk for forensic workers, among other healthcare providers. The risk of contamination is serious in post-mortem procedures. SARS-CoV2 is a microorganism classified as Hazard Group 3. However, the lack of adequate scientific work on Covid-19 should prompt us to be even more cautious when handling potentially infected persons or materials. Before starting the post-mortem investigation a risk assessment should be carried out and the suitability of facilities, personnel and equipment should be evaluated. An autopsy room conforming to BSL 3 standards would be ideal but is not mandatory. For suspicious or approved cases however a number of procedural changes must be made concerning the body's removal, storage and inspection procedures. Facilities, equipment and training issues need to be revised against existing and potential risks of infection. In addition to proper ventilation and insulation, personal protective equipment, aerosol reduction measures and disinfection applications are required. As of yet it is still unclear how long this public health issue, which has grown to become a pandemic, will last. This article highlights preventive measures to be taken into consideration in post-mortem processes when a Covid-19 infection is suspected or confirmed. It should be noted that there is no standard guide yet in this regard. A guide should be created according to international standards and revised according to changing conditions.